Unity of spiritual and moral values and educational philosophy of Immanuel Kant (Journal of Philosophy Culture and Political Science, 2015)
In the article the idea of the unity of philosophical and pedagogicalthinking of Kant, which follows from the Kantian moral and philosophicalreflections. Education Kant – the formation of morality, preservation of autonomyand freedom. The starting point is the argument of Kant’s anthropologicaldefinition that only by educating people to become human. Kantorganizes tasks of education: discipline, culture, civilization, introductionto civilization and morality in the sense of the categorical imperative. Themeasure of education – a subject that is configured to himself as a manwho saves his freedom of independent thinking and thus your mind. Thepurpose of education – to direct the human race for excellence, facilitatethe implementation of a man of his appointment, to cultivate their humannature
Keywords: I. Kant; education; values; civilization; categorical imperative.